Using Association Rules to Enrich Arabic Ontology - Ksiksi, A.; Amiri, H. (Engineering, Technology & Applied Science Research, 2018)
In this article, we propose the use of a minimal generic base of associative rules between term association rules, to automatically enrich an existing domain ontology. Initially, non-redundant association rules between terms are extracted from an Arabic corpus. Then, the matching of the candidate terms is done through the matching between the concepts of the initial ontology and the premises of the association rules, with three distance measures that we define.